Effect of energy band misalignment and morphology in In2O3-CNTs on electron transport in dye-sensitized solar cell - Mahalingam S.; Abdullah H.; Manap A. (Taylor and Francis Inc., 2023)
Alignment; Band structure; Electron transport properties; Indium compounds; Morphology; Multiwalled carbon nanotubes (MWCN); Chemical bath deposition technique; Electron lifetime; Electron recombinations; Electron transport; Optimum concentration; Performance degradation; Photo-anodes; Power conversion efficiencies; Dye-sensitized solar cells